Control de Echinochloa colona con la aplicación de diferentes ingredientes activos en el cultivo de arroz (Oryza sativa L.) en Babahoyo - Latacela Coello, Ana Karina (2019)
VIII. SUMMARY The present experimental work was established in the Rcto. "Nuevo Progreso", owned by Mr. Luis Contreras, located at km 2.7 of the Babahoyo-La Chorrera road, between the geographic coordinates of 277438.27 UTM of west longitude and 110597.98 UTM of south latitude, the area It is located at a height of 8m.snm The zone presents a humid tropical climate, with an average annual temperature of 25.40 ° C; an annual rainfall of 2048.80 mm, humidity 79% and 725.10 hours of annual average heliophany. The soil has a flat topography, a loamy clay texture and regular drainage. The INIAP 15 rice seed was used as the study material. The treatments consisted of herbicides in different doses and absolute and conventional control, such as Brioso 800 (Propanil) in doses of 5.0 L / ha; Mapcid (Fenoxaprop ethyl), in a dose of 1.0 L / ha; Kloner (Cihalofop butyl ester), dose of 1.5 L / ha; Mapclorax (Quinclorac) in doses of 2.0 L / ha; Launches 400 (Bispyribac sodium) in doses of 0.75 L / ha; Aura (Profoxydim) in doses of 0.75 L / ha; Without product (absolute control) and manual control (conventional control). The experimental design of Complete Blocks at Random was used, with eight treatments and three repetitions. The evaluated variables were subjected to the analysis of variance and the comparison of means was made with the Tukey significance test at 95% probability. All the necessary agricultural work was carried out in the cultivation of rice for its normal development, such as land preparation, sowing, irrigation, fertilization, weed control, phytosanitary control and harvesting. Based on the results obtained, it was determined that there was control of Echinochloa colona with the application of different herbicides in the cultivation of rice (Oryza sativa L.) in Babahoyo; the applied herbicide products did not cause toxicity in the crop, they reported good weed control; the highest plant height, number of tillers and panicles / m2, length of panicles, grains per panicles and weight of 1000 grains recorded better averages with the use of Lanza 400 (Bispyribac sodium) in doses of 0.75 L / ha and the Use of Lanza 400 (Bispyribac sodium) in doses of 0.75 L / ha reached higher yield and net benefit with 4823.3 kg / ha and $ 289.87.